Multidimensional Data Analysis: An Application to the Study of the Relationship Between Children’s Peer Collaboration and Socioeconomic Context - Curcio, Juan Manuel (2018)
This paper proposes and illustrates the use of the French version of the multidimensional data analysis (MDA) as an alternative approach for analyzing quantitative data in social sciences, particularly in psychology. To that end, we revisited a previous research which analyzed children’s peer collaboration in a task involving building a house with construction blocks in two socioeconomic contexts (SEC): advantaged socioeconomic context (ASC) and disadvantaged socioeconomic context (DSC). The social modality of task execution and the types of message were analyzed. The results from the ASC (associated with explicit cooperation and collaboration) were contrary to those of the DSC (linked to implicit cooperation). These results are consistent with those from previous studies, for both SECs register similar levels of social coordination, but the specific interaction modality is different. This kind of analytical tools is particularly important in social sciences due to the complexity of the objects of study and the resulting possibility to achieve more comprehensive exploratory approaches.